Governance of electoral preferences: consensus expectations and voting intention in students of a public university (2019)
The objective of this work was to validate a predictive model of voting intention. An exploratory, cross-sectional and correlation study was carried out with an intentional sample of 253 students from a public university, considering the intensive use of electronic networks. Three factors were found that explained 70 % of the variance. Although the research design limits the results to the study sample, the extension of the model to other scenarios is suggested.